2013
DOI: 10.4317/medoral.17998
|View full text |Cite
|
Sign up to set email alerts
|

Simulation for training in oral cancer biopsy: A surgical model and feedback from GDPs

Abstract: Objectives: To describe a new bench model for oral precancer/cancer biopsy training and to assess its effectiveness in terms of trainees’ perception. Study design: Cross-sectional, descriptive, performed on 424 general dental practitioners (GDP) who undertook biopsies on a pig tongue. The participants were assessed by direct observation for 2.5 hours using specific check-lists and by means of a self-applied questionnaire. Results: The workshop was perceived as “very interesting” even by those with previous su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…(10) It has been reported that theoretical and practical training workshops could enhance the ability of general dental practitioners in oral biopsy. (11) Therefore, it is crucial to gain a complete understanding of artifacts and take appropriate preventive measures. (1) Since artifacts frequently occur in oral biopsy, (12,13) and there are very few studies comprehensively exploring the oral biopsy artifacts, (10) it was felt that a detailed in-…”
mentioning
confidence: 99%
“…(10) It has been reported that theoretical and practical training workshops could enhance the ability of general dental practitioners in oral biopsy. (11) Therefore, it is crucial to gain a complete understanding of artifacts and take appropriate preventive measures. (1) Since artifacts frequently occur in oral biopsy, (12,13) and there are very few studies comprehensively exploring the oral biopsy artifacts, (10) it was felt that a detailed in-…”
mentioning
confidence: 99%
“…Such training programs are particularly beneficial for professionals working in remote areas, as is the case in some countries like Brazil. In Spain, professionals who had participated in continuing education courses were almost four times more likely to perform biopsies on suspicious lesions 30,31 , demonstrating the positive impact of professional updates. Despite the study's limitations, the results suggest a clear need to include oral biopsy clinical skills workshops as a supplementary educational resource for the continuing education of all dental professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Only one simulation method for teaching oral biopsies has been reported in the literature 1 . This employed pig tongues, which may not be feasible for all academic institutions.…”
Section: Problemmentioning
confidence: 99%
“…Only one simulation method for teaching oral biopsies has been reported in the literature. 1 This employed pig tongues, which may not be feasible for all academic institutions. Also, the use of an animal model leads to the absence of an anatomical simulation.…”
Section: Problemmentioning
confidence: 99%